Upaya Pencegahan Perceraian pada Kantor Urusan Agama Kecamatan Lawe Bulan - Jamilah Jamilah; Suarni Abdullah; Husni Bin Abdul Jalil (AHKAM, 2026)
The increasing number of divorce cases in Aceh Tenggara Regency, which reached 286 cases in 2024, indicates that divorce prevention efforts require serious attention. In this context, the Kantor Urusan Agama (KUA) has a strategic role as the frontline institution for preventing divorce, one of which is through premarital guidance as stipulated in Keputusan Direktur Jenderal Bimbingan Masyarakat Islam Kementerian Agama Nomor 379 Tahun 2018. This study aims to examine the efforts made by KUA Lawe Bulan, Aceh Tenggara Regency, in preventing household divorce within its working area. This study employed a normative-empirical legal method by utilizing primary data obtained through interviews with informants at KUA Lawe Bulan as well as secondary data derived from laws and regulations. The results show that KUA Lawe Bulan implements four main programs in its divorce prevention efforts, namely strict document screening, premarital guidance, post-marital counseling, and mediation for households experiencing conflict. These efforts proved effective, as indicated by the achievement of reconciliation in several cases of household disputes. These findings contribute to strengthening the study of Islamic family law and sociology, affirming the relevance of the normative-empirical approach in analyzing divorce prevention practices within social, cultural, and institutional contexts, while also providing practical implications for KUA Lawe Bulan and BP4 in formulating more effective family development strategies. This study concludes that the BP4 program at KUA Lawe Bulan has a positive impact in helping couples resolve household conflicts and improve the quality of marriage, while also opening opportunities for further research on the roles of religious leaders, customary leaders, religious counselors, and village governments in supporting divorce prevention efforts.